«Husbond» fru Dorthe Juel: En adelskvinnes autoritetsroller ved inngangen til 1600-tallet - Ellefsen, Irene Almkvist (Tidsskrift for kulturforskning, 2025)
This article examines the authority of noblewomen who owned estates in early modern Norway. The actions and agency of these women had significant impacts on their families and local communities. In Scandinavia, a few noblewomen were also granted fiefs. Holding a fief was one of several authoritative roles occupied by noblewomen in the late 16th and early 17th centuries, closely linked to aristocratic culture. This article focuses on the case of Dorthe Nielsdotter Juel, who was the fief owner of Onsøy in southeastern Norway from 1588 to 1596. It explores how her authority was manifested in various roles: as a fief holder, estate owner, family matron, and lay patron, and examines these within the context of research on elite women’s agency in the early modern period. How do historical sources reflect whether Dorthe was treated according to the norms of gender or social class? By analyzing how Dorthe’s authority is depicted in contemporary written sources, we can explore how she leveraged her authority to influence the local community and her family. Analyzing these sources supports the idea that gender norms were flexible, and that the expectations for a female estate owner focused on fulfilling the responsibilities of the office and role, regardless of gender.